EFFECT OF PRECIPITATION ON RIO GRANDE WILD TURKEY POULT PRODUCTION IN TEXAS - T. Wayne Schwertner; Markus J. Peterson; Nova J. Silvy (Wildlife Society Bulletin)
Abstract: Precipitation can strongly influence the population dynamics of gallinaceous birds in semiarid regions. Little is known, however, about the interaction of precipitation and Rio Grande wild turkey (Meleagris gallopavo intermedia; RGWT) production in Texas, particularly across broad spatial and temporal scales. We compared RGWT production data with precipitation and drought data across 5 ecological regions of Texas for 1976–2000. Poult production was positively correlated with both the June Modified Palmer Drought Severity Index (PMDI) and September–June raw precipitation in all ecological regions. We found weaker correlations with June raw precipitation in all ecological regions except the Post Oak Savannah, and with cumulative September–June PMDI in the Edwards Plateau, Cross Timbers and Prairies, and South Texas Plains. Our results indicate that poult production is more influenced by cumulative weather effects over several months than by individual rainfall events, suggesting that direct precipitation‐induced mortality does not substantially affect RGWT production in Texas. Further, precipitation data provides managers with an inexpensive, effective indicator of RGWT production in Texas.